Elementary Teachers’ Perception on the Implementation of Mother Tongue-Based Multilingual Education in Zamboanga City - Quitiol, Phil Argel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the perceptions of seasoned public elementary school teachers regarding the implementation of Mother Tongue-Based Multilingual Education (MTB-MLE) in Zamboanga City. Anchored on Krashen’s Second Language Acquisition Theory, Skinner’s Operant Conditioning Theory, and Piaget’s Cognitive Development Theory, the study explored teachers’ perceptions, experiences, challenges, coping mechanisms, and recommendations for improving MTB-MLE implementation. A phenomenological qualitative research design was employed. Data were collected through semi-structured, one-on-one interviews using an expert-validated interview guide with seasoned public elementary school teachers from Canelar Integrated School who had at least 20 years of teaching experience and were using Chabacano as the medium of instruction. The data were analyzed through thematic analysis. The findings revealed that teachers perceived MTB-MLE as beneficial for Chabacano-speaking learners because it enhanced comprehension, classroom participation, and language preservation. However, they also identified challenges in multilingual classrooms, particularly language barriers among non-Chabacano-speaking learners and the shortage of teaching materials and instructional resources. Teachers addressed these challenges through translation, remedial instruction, parental involvement, resourcefulness in developing instructional materials, and continuous language practice. The study concludes that while MTB-MLE supports meaningful learning among native Chabacano speakers, its implementation requires stronger instructional support and greater responsiveness to learners’ linguistic diversity. It recommends recognizing learners’ actual mother tongues, strengthening instructional resources, enhancing teacher training, improving remediation and translation support, and offering Chabacano as a separate subject. The study aligns with Sustainable Development Goals 4 (Quality Education), 10 (Reduced Inequalities), and 17 (Partnerships for the Goals). Its findings contribute to educational, institutional, policy, and community sustainability by supporting improvements in instructional practices, teacher development, educational governance, and language preservation in multilingual learning environments.